Effect of Coal Grain Size on Sorption Capacity with Respect to Propylene and Acetylene - Agnieszka Dudzińska; Natalia Howaniec; Adam Smoliński (Energies, 2017)
Propylene and acetylene are released to mine air with the increase in the temperature of self-heating coal. Concentrations of these gases in mine air are applied as indicators of the progress of the self-heating process. Hydrocarbons emitted from the self-ignition center are sorbed on coal, while migrating through the mine workings. Coal crushed during the mining process is characterized by a high sorption capacity, which facilitates the sorption phenomena. This results in the decrease in hydrocarbons content in mine air, and in the subsequent incorrect assessment of the development of the self-heating process. The results of the experimental study on propylene and acetylene sorption on Polish coals acquired from operating coal mines are presented in this paper. Bituminous coal is characterized by a high sorption capacity with respect to unsaturated hydrocarbons, like propylene and acetylene. The sorbed volumes depend on the grade of metamorphism, porosity, and chemical characteristics of coal. Low level of metamorphism, increased porosity, and oxygen content result in higher sorption capacity of coals. The reduction in grain size of coals also results in the increased sorption capacity with respect to hydrocarbons. The most significant increase in the volumes of sorbed propylene and acetylene with the decrease in grain class was observed for coals of low porosity, high grade of metamorphism, and low to medium sorption capacities. The 10-fold decrease in coal grain size resulted in the 3 to 6-fold increase in the volume of sorbed propylene, and 2-fold increase for acetylene. The decrease in grain size results in higher accessibility of pore structure, increased pore volume and area, and higher number of active centers interacting with hydrocarbons of dipole characteristics. For coals with low grade metamorphism, high porosity, and high sorption capacity the volumes of sorbed propylene and acetylene increased only slightly with the decrease in coal grain size.